'She is looking at me! Shall I share?' How Chinese and American preschoolers respond to eye gaze during sharing. Issue 2 (5th January 2018) - Wu, Zhen; Chen, Xi; Gros‐Louis, Julie; Su, Yanjie
Abstract: Previous research shows that the recipient's verbal communication about desires increases young children's sharing behavior. The current study examined how an adult partner's non‐verbal communication through eye gaze influenced sharing behavior in children from different cultures. We presented one hundred forty‐six 3‐ to 5‐year‐old American and Chinese children with a Dictator Game, in which they were asked to distribute resources between themselves and an experimenter. Children were randomly assigned to three conditions, in which the experimenter alternated her gaze between the child and the items that she wanted, or looked randomly around the room, or left when the child made decisions about sharing but claimed to come back later. Results showed that Chinese children shared more than American children did in the alternating‐gaze condition, but not in the other two conditions; furthermore, the experimenter's alternating gaze influenced Chinese children to be more generous, but had no significant effect on American children. This suggests that compared to American children, Chinese children may be more compliant with others' requests communicated through a subtle cue of eye gaze. The study demonstrates important differences in sharing behaviors between American and Chinese preschoolers, and these differences are consistent with the cultural constructs of individualism and collectivism.